Kebijakan Hukum Pemerintah Dalam Mengatasi Plastik Sekali Pakai Dan Dampaknya Terhadap Lingkungan - Muhammad Fahrudin; Irwan Triadi (Lembaga Pengembangan Kinerja Dosen, 2024)
The issue of plastic bags continues to be a significant topic globally in waste management. Their relatively low cost, ease of use, and accessibility have made plastic bags an integral part of human life. With increasing plastic bag usage, inevitably comes an increase in plastic waste. Moreover, the rapid usage cycle of plastic bags, as they are typically single-use items used only temporarily, exacerbates the problem. If plastic waste is not optimally managed, it will have negative environmental impacts. To address this, the retail company Alfamart has begun employing green marketing strategies to promote the